An endothelium-derived hyperpolarizing factor distinct from NO and prostacyclin is a major endothelium-dependent vasodilator in resistance vessels of wild-type and endothelial NO synthase knockout mice - Brandes, Ralf P. (The National Academy of Sciences, 2000)
In addition to nitric oxide (NO) and prostacyclin (PGI(2)), the endothelium generates the endothelium-derived hyperpolarizing factor (EDHF). We set out to determine whether an EDHF-like response can be detected in wild-type (WT) and endothelial NO synthase knockout mice (eNOS −/−) mice. Vasodilator responses to endothelium-dependent agonists were determined in vivo and in vitro. In vivo, bradykinin induced a pronounced, dose-dependent decrease in mean arterial pressure (MAP) which did not differ between WT and eNOS −/− mice and was unaffected by treatment with N(ω)-nitro-l-arginine methyl ester and diclofenac. In the saline-perfused hindlimb of WT and eNOS −/− mice, marked N(ω)-nitro-l-arginine (l-NA, 300 μmol/liter)- and diclofenac-insensitive vasodilations in response to both bradykinin and acetylcholine (ACh) were observed, which were more pronounced than the agonist-induced vasodilation in the hindlimb of WT in the absence of l-NA. This endothelium-dependent, NO/PGI(2)-independent vasodilatation was sensitive to KCl (40 mM) and to the combination of apamin and charybdotoxin. Gap junction inhibitors (18α-glycyrrhetinic acid, octanol, heptanol) and CB-1 cannabinoid-receptor agonists (Δ(9)-tetrahydrocannabinol, HU210) impaired EDHF-mediated vasodilation, whereas inhibition of cytochrome P450 enzymes, soluble guanylyl cyclase, or adenosine receptors had no effect on EDHF-mediated responses. These results demonstrate that in murine resistance vessels the predominant agonist-induced endothelium-dependent vasodilation in vivo and in vitro is not mediated by NO, PGI(2), or a cytochrome P450 metabolite, but by an EDHF-like principle that requires functional gap junctions.